2013
DOI: 10.1016/j.appet.2012.04.017
|View full text |Cite
|
Sign up to set email alerts
|

Systematic reviews of the evidence on the nature, extent and effects of food marketing to children. A retrospective summary

Abstract: A 2009 systematic review of the international evidence on food and beverage marketing to children is the most recent internationally comprehensive review of the evidence base. Its findings are consistent with other independent, rigorous reviews conducted during the period 2003-2012. Food promotions have a direct effect on children's nutrition knowledge, preferences, purchase behaviour, consumption patterns and diet-related health. Current marketing practice predominantly promotes low nutrition foods and bevera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

16
555
1
18

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 602 publications
(590 citation statements)
references
References 29 publications
16
555
1
18
Order By: Relevance
“…High levels of dental caries and increases in weight have sharpened the focus at the national and supranational levels on the relationship between advertising and negative health outcomes. Extensive literature reviews have found an association between exposure to advertising for foods HFSS and poor diet and obesity (Cairns et al, 2013;Hastings et al, 2003;McGinnis et al, 2006). The authors concluded that the effects of advertising exposure on diet are not due to chance.…”
Section: Relationship Between Food and Beverage Advertising And Childmentioning
confidence: 99%
“…High levels of dental caries and increases in weight have sharpened the focus at the national and supranational levels on the relationship between advertising and negative health outcomes. Extensive literature reviews have found an association between exposure to advertising for foods HFSS and poor diet and obesity (Cairns et al, 2013;Hastings et al, 2003;McGinnis et al, 2006). The authors concluded that the effects of advertising exposure on diet are not due to chance.…”
Section: Relationship Between Food and Beverage Advertising And Childmentioning
confidence: 99%
“…Additional mechanisms for marketing to children extend to the school environment as well as Internet and social media realms (10,11) . Advertising to children is worrisome due to the strong body of evidence demonstrating that marketing exposure has a negative impact on diet and weight (1,12) . In fact, in 2010, the WHO released a set of recommendations to restrict marketing of foods high in saturated fat, trans-fat, added sugar or salt to children (13) .…”
mentioning
confidence: 99%
“…1,5,19,20,26,27 Strong evidence supports that exposure to childdirected food advertising influences a child's food requests, 7 and childdirected television advertisements are often crafted to increase children's pestering for advertised products. 1 However, parents may perceive children's foods as low in nutrition and high in sugar based on characteristics of child-directed advertisements 11 and product packaging, 28 such as bright colors, animation, and licensed characters.…”
Section: Discussionmentioning
confidence: 99%